Regional sectoral analysis in support of the human settlements sector - Da Costa, Jackie (CCS GeorgetownGY, 1993)
Reviews critical sectoral issues such as capacity building, training requirements, institutional arrangements for regional sectoral policy coordination and horizontal cooperation. Identifies areas suitable for technical cooperation at a regional level.